WATCHMAN versus ACP or amulet for left atrial appendage closure. Results from the LAARGE registry. (25th November 2020) - Ledwoch, J; Franke, J; Akin, I; Geist, V; Weiss, C; Zeymer, U; Pleger, S; Hochadel, M; Mudra, H; Senges, J; Lewalter, T; Brachmann, J; et al.
Abstract: Background: Several left atrial appendage (LAA) closure systems are available and due to differences in device design safety and efficacy of specific occluders derived from trials cannot be simply generalized to all devices. Purpose: The present analysis sought to assess two contemporary LAA closure devices in clinical practice. Methods: The present work represents a non-randomized sub-analysis of the prospective, multicenter, Left-Atrium-Appendage Occluder Register - GErmany (LAARGE) registry. The WATCHMAN (group 1) and the Amplatzer Cardiac Plug (ACP) or Amulet occluder (group 2) were assessed regarding technical success and procedural safety. Results: A total of 641 patients at 38 centers were enrolled. Of them, 278 (43%) and 340 (53%) patients received the WATCHMAN and ACP/Amulet occluder, respectively. High technical success was achieved with a slight difference between the groups (96% in group 1 vs. 99% in group 2; p=0.007). Procedural safety did not differ (98% in group 1 vs. 97% in group 2; p=0.55). Chicken wing morphology of the LAA seemed to trigger the use of the ACP/Amulet (chicken wing in 36% of the cases in group 1 vs. 55% in group 2; p<0.001). The Kaplan Meier estimated 1-year composite of death or stroke was 12.0% and 12.9%, respectively (Figure 1A). The respective rates for the composite endpoint of death, stroke or systemic embolism were 12.0% and 13.2% (Figure 1B). Conclusions: Both the WATCHMAN and the ACP/Amulet occluder provide excellent procedural results with comparable implantation success and no differences regarding procedural safety and long-term effectiveness. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Stiftung Institut für Herzinfarktforschung (IHF)